Professional training of students majoring in physical education: the role of the state exam - Nikolenko Yu.F. ,; Shibaeva A.A. ,; Ovchinnikova E.I. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to evaluate the preparedness of students in the field of physical education for their future careers, we will conduct a comprehensive assessment during the state examination. Methods and structure of the study. The research work was carried out with the participation of 2024 bachelor's degree graduates of the Transbaikal State University in the field of «Pedagogical Education» in the amount of 43 full-time and part-time students. Using the mechanism of independent assessment of qualifications at open meetings of state examination commissions, the indicators of the theoretical and methodological, project-technological, practical and activity components of readiness for professional activity of graduates were studied. Results and conclusions. The process of developing a teacher's professional preparedness for teaching involves a series of stages, spanning a considerable timeframe. These stages include pre-professional training, obtaining specialized pedagogical education through secondary vocational and higher education institutions, and engaging in actual teaching, during which teachers are required to enhance their skills. Based on the established methodology for assessing the outcomes of the state examination, the level of preparedness of physical education graduates for professional work is determined. The examination reveals the indicators of theoretical and methodological, design and technological, and practical and activity-based preparedness of physical education graduates. Additionally, differences in the structure of readiness for professional work between full-time and part-time students were identified. The interdependence between the theoretical and methodological, design and technological, practical and activity, and initial physical fitness indicators (as measured by the entrance tests in physical education) has been identified, and the extent to which these indicators affect the preparedness of physical education graduates for their professional careers has been assessed.